ENHANCING MENTOR TEACHERS’ COMMITMENT IN DURING TEACHING PRACTICE IN TEACHER EDUCATION PROGRAMMES: FACTORS, FINDINGS, AND RECOMMENDATIONS (Unilorin Journal of Lifelong Education, 2025)
This study utilized a descriptive survey design to examine mentor teachers’ level of commitment to teaching during teaching practice in teacher education programs. three research questions were raised for the study. The population were the pre-service teachers in faculty of education from three purposively sampled Universities in Ilorin. While the target population were the 400 level pre-service teachers from the sample institutions. The 400 level students were 3861 out of which 641 were sample using proportionate sampling procedure. A researcher-designed Likert scale questionnaire with a psychometric properties of content validity and a reliability index of 0.73 was the instrument used to elicit the needed data. Descriptive statistics was used to analyse the data collected. Findings revealed that the level of commitment mentor teachers is low, and it is influenced by factors such as inadequate facilities, low qualifications, and poor remuneration. Recommendations include implementing mentor training programs, enhancing school facilities, and establishing clear selection criteria for mentor teachers. Addressing these factors is essential for improving the mentorship experience and enhancing the quality of teaching practice for pre-service teachers. By enhancing mentor teachers’ commitment and support, teacher education programs can better prepare aspiring educators for their future roles.